Degeneration of Hitchin representations along internal sequences - Zhang, Tengren (Geometric and functional analysis, 2015)
We first give a coordinate system on the P S L ( n , R ) Hitchin component that is a direct analogue of the Fenchel–Nielsen coordinates on Teichmüller space. Using these coordinates, we consider a class of sequences in the Hitchin component, called internal sequences, along which most length functions grow to infinity and the topological entropy of the associated geodesic flow converges to 0.